2009
DOI: 10.1007/s10900-009-9186-0
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle-Related Determinants of Hookah and Cigarette Smoking in Iranian Adults

Abstract: To identify lifestyle-related determinants of hookah and cigarette smoking in Iranian adults, a total of 12,514 men and women aged >/=19 years in three counties in central Iran (Isfahan, Najafabad, Arak) were selected in multistage random sampling. Data on socio-demographic characteristics and lifestyle were collected in interviewer-administered questionnaires, as part of the baseline survey of the Isfahan Healthy Heart Program. Unhealthy lifestyle-related factors independently associated with cigarette and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 23 publications
6
25
2
1
Order By: Relevance
“…In agreement with previous studies (15)(16)(17)(18)(19), our results show that the waterpipe tobacco smoking rate among Iranians is increasing each year, and this could be due to the failure of Iranian tobacco control programmes in the field of waterpipe smoking. It should be noted that due to the differences in the methods and sample sizes, these studies are not fully comparable; however, the increasing trend of consumption is inferable.…”
Section: ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫العرشون‬ ‫و‬ ‫الثالث‬ ‫اsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies (15)(16)(17)(18)(19), our results show that the waterpipe tobacco smoking rate among Iranians is increasing each year, and this could be due to the failure of Iranian tobacco control programmes in the field of waterpipe smoking. It should be noted that due to the differences in the methods and sample sizes, these studies are not fully comparable; however, the increasing trend of consumption is inferable.…”
Section: ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫العرشون‬ ‫و‬ ‫الثالث‬ ‫اsupporting
confidence: 92%
“…Almost half of the participants had the experience of waterpipe smoking at some point in their lives, with current smokers accounting for 17.6%. According to the results of a study done in the Islamic Republic of Iran, 1% of participants were daily waterpipe smokers (15). The A few values missing in some categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase shown in our study also may support the findings of the previously mentioned study which claimed that 18.5% of students who had previously never smoked WP turned into WP experimenters (even one or two puffs) and 1.5% of WP experimenters turned into regular WP users (current WP smokers) [34]. According to a study that was done in Tehran in 2012, the prevalence of WP smoking among women 15-24 years age was 6.9% [40] and in the southern cities in Iran, it was 8.2% [41]. The national GYTS survey that was done in 2007 in Iran among 1 996 middle-school students aged 13-15 showed that 43.8% of students had smoked WP at least once, of whom 55% were males and 32% were females, and 16.5% were current WP smokers, of whom 22.8% were males and 9.4% were females [19].…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, the prevalence rate of hookah smoking was reported 5.3% across the entire country and 8.2% in the southern cities. 8,9 There is limited information about illicit drug use and associated factors in hookah smokers in Iran. So, the aim of this study was to assess the status of illicit drug use and associated factors among hookah smokers of Khalil Abad city in 2015.…”
Section: Introductionmentioning
confidence: 99%